Is there life after Buckley’s formocresol? Part II – Development of a protocol for the management of extensive caries in the primary molar - V. SRINIVASAN, C. L. PATCHETT, & P. J. WATERHOUSE (Paediatric Dentistry, 2006)
To produce a working clinical protocol for pulp therapy techniques in the extensively carious primary molar.